138k views
2 votes
Simplify the expression below and explain your steps. x/2=x/8

1 Answer

2 votes

Answer:

x2-x-8=0

Explanation:

The first term is, x2 its coefficient is 1 .

The middle term is, -x its coefficient is -1 .

The last term, "the constant", is -8

Step-1 : Multiply the coefficient of the first term by the constant 1 • -8 = -8

Step-2 : Find two factors of -8 whose sum equals the coefficient of the middle term, which is -1 .

-8 + 1 = -7

-4 + 2 = -2

-2 + 4 = 2

-1 + 8 = 7

User Nbaosullivan
by
5.3k points